The sovereignty of blockchain dispute resolution - Nima Norouzi (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2022)
Blockchain technology acts as the infrastructure for self-executing smart contracts. However, because contracts are flawed, and some parties are opportunistic, these new contract options have created challenges in resolving disputes. For example, will smart contracts be recognized and any disputes (in this regard) resolved in existing courts in the jurisdiction? In this article, we first outline some organizational governance options (e.g., mediation, private arbitration, courts) to create a boundary of possibility (option) of resolving disputes for the parties. Second, we provide case studies of emerging blockchain-based mechanisms for resolving dispute resolution challenges. Blockchain-based smart contracts may create dispute resolution problems and act as a technology for entrepreneurs to create new mechanisms for resolving disputes, including those arising from traditional legal contracts. The parties to the contract will inherently choose their most effective governance mechanism for resolving disputes and will change the costs of resolving disputes over time through a process of institutional innovation.